Analisis Life Cycle Cost pada Pembangunan Gedung Polres Buton Utara - Lisman, Lisman; Isazarni Jassin, Andi Makkawaru; Sufrianto, Sufrianto (Universitas Sulawesi Tenggara, 2025)
The existence of the building plays an important role in human life, in accordance with the designation the building was built. After completion, a building is expected to fulfill its function according to the planned age. However, in line with the increasing age of a building, the performance of building construction decreases due to various factors, including the use of inappropriate materials, environmental factors around the building and the age of building components that have reached their useful life. The purpose of the study was to analyze the life cycle cost of the construction of the North Buton Police Station building and find out what cost components were involved in the construction of the North Buton Police Station building and to determine the ratio of each component of the life cycle cost to the construction of the North Buton Police Station building. Based on the results of the data analysis, it shows that the actual life cycle cost of the North Buton Police Building is Rp. 54.025.562.266,69,- with the following details: Initial cost is Rp. 25.112.157.000,00 (46.48%), operational costs are Rp. 8.350.834.784,44 (15.46%), maintenance and replacement costs of Rp. 19.967.052.142,10 (36.96%), and demolition costs of Rp. 595.518.340,15 (1.10%). Floor Components obtain the highest maintenance costs, namely Rp. 4.971.573.277,35 (41.21%) of the Total Value of Structural Components Maintenance being reviewed. The ratio of Total Operating Costs, Maintenance and Replacement Costs, and Dismantling Costs to initial costs is 53,52% and 46,48%